ETHNIC DIFFERENCES IN NUTRITIONAL STATUS IN ADOLESCENTS FROM REPUBLIC OF NORTH MACEDONIA - Bojadzieva, Biljana Stojanoska; Matveeva, Niki; Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Kordoska, Jovana; Angelovska, Irina; Pejkovska, Sava; Kavecan, Ivana; Dimcheva, Anita; Antova, Emilija (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
The aim of the study was to evaluate ethnic differences of nutritional status among the adolescents from Republic of North Macedonia. This study included 2386 adolescents (1762 of Macedonian ethnic group and 624 of Albanian ethnic group) of both sexes, at the age from 11 to 18 years. Body height and weight were measured using standard equipment and measurement technique. Body mass index (BMI) was calculated (kg/m 2 ) as anthropometric indicator for evaluating nutritional status in adolescents .We found ethnic differences in nutritional status in both male and female adolescents of both Macedonian and Albanian ethnic group. The percent of underweight adolescents in the first group at the age from 11 to 14 years and in the second group at the age from 15 to 18 years was higher in Albanian adolescents in both sexes.On the other hand males and females of Macedonian ethnic group were with higher percent with risk of obesity and overweightwith BMI>95 th percentile. There were statistically significant differences in nutritional status in adolescents of both ethnic groups in Republic of North Macedonia and the obtained values in our study are recommended to be applied for better understanding of deviations in growth and nutrition in both ethnic groups. Key words: adolescents, ethnic groups, nutritional anthropometry, body height, body weight